The presence of prolines in the flanking region of an immunodominant HIV‐2 gag epitope influences the quality and quantity of the epitope generated. Issue 8 (24th June 2015) - Jallow, Sabelle; Leligdowicz, Aleksandra; Kramer, Holger B.; Onyango, Clayton; Cotten, Matthew; Wright, Cynthia; Whittle, Hilton C.; McMichael, Andrew; Dong, Tao; Kessler, Benedikt M.; Rowland‐Jones, Sarah L.
<x xml:space="preserve">Abstract</x> Both the recognition of HIV‐infected cells and the immunogenicity of candidate CTL vaccines depend on the presentation of a peptide epitope at the cell surface, which in turn depends on intracellular antigen processing. Differential antigen processing maybe responsible for the differences in both the quality and the quantity of epitopes produced, influencing the immunodominance hierarchy of viral epitopes. Previously, we showed that the magnitude of the HIV‐2 gag‐specific T‐cell response is inversely correlated with plasma viral load, particularly when responses are directed against an epitope, 165DRFYKSLRA173, within the highly conserved Major Homology Region of gag‐p26. We also showed that the presence of three proline residues, at positions 119, 159 and 178 of gag‐p26, was significantly correlated with low viral load. Since this proline motif was also associated with stronger gag‐specific CTL responses, we investigated the impact of these prolines on proteasomal processing of the protective 165DRFYKSLRA173 epitope. Our data demonstrate that the 165DRFYKSLRA173 epitope is most efficiently processed from precursors that contain two flanking proline residues, found naturally in low viral‐load patients. Superior antigen processing and enhanced presentation may account for the link between infection with HIV‐2 encoding the "PPP‐gag" sequence and both strong gag‐specific CTL responses as well as lower viral load.